Bridging Law and Astronomy: The Influence of Astronomy on Islamic Law - Anwar Anwar; Bukhari Bukhari; Andi Mardika (Astroislamica: Journal of Islamic Astronomy, 2024)
This paper explores the deep relationship between Islamic astronomy ( Ilm al-Falak ) and Islamic law, highlighting its influence on the determination of prayer times, the Qibla direction, and its role in Islamic legal decision-making. This study employs a qualitative method with a descriptive-analytical approach. It draws upon both classical and modern literature, as well as documented expertise from scholars of Islamic astronomy and Islamic law, to provide a comprehensive understanding. The results show that Islamic astronomy has enriched and enhanced the practice of Islamic law, particularly in accurately determining prayer times and the Qibla direction. However, challenges remain in harmonizing Islamic astronomy with Islamic law, necessitating ongoing dialogue between religious scholars and astronomers.